Estimulate the reading comprehension. (Journal of Parents and Teachers, 2013)
This article talks about the development of children’s Reading Comprehension and the importance of parents in this process. Reading Skill is an endless learning that is developed during the whole life. The main problem arisen in this learning process, happens when Reading is exclusively focused on school. Parents play an important role in this issue in order to stimulate and to improve child’s learning. The article’s authors suggest some games and examples to parents for carrying them out with their children, such as vocabulary learning. Lastly, the most common mistakes and factors that affect children in their Reading process are explained and in which way children respond.
Keywords: Reading Comprehension. Learning process; Children; Parents influence; Education.